Paris and Everywhere Else - Kaelen Wilson-Goldie (Manazir Journal)
Saliba Douaihy, Shafic Abboud, and Saloua Raouda Choucair were three Lebanese artists who traveled to Paris in the process of becoming canonical artists in their home country. But Paris was not their only destination. For all three of these artists, their intercity movements produced an experience of cosmopolitanism that was circulatory and nonhierarchical. This cosmopolitanism did not flow only one way. Rather, it pooled as artists took advantage of opportunities to travel and moved back and forth between different transnational hubs. This article explores how cosmopolitanism operates, as a pattern of movements and a mode of exchange, and questions the connections among cosmopolitanism, modernism, and abstraction. Drawing on recent scholarship to define cosmopolitanism as a mixture of languages and a density of encounters, I argue that artists such as Douaihy, Abboud, and Choucair exemplified the linguistic phenomenon of heteroglossia in the visual arts. These artists approached abstraction not as a style to imitate but rather as a language to use, one easily interchangeable with the others they already spoke fluently. I propose that if we, too, approach abstraction, metaphorically, in linguistic rather than stylistic terms, then we will develop the tools to reformulate modernism as expansively global.